If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + -1(15x + -1) = -2v + -8 Reorder the terms: -5 + -1(-1 + 15x) = -2v + -8 -5 + (-1 * -1 + 15x * -1) = -2v + -8 -5 + (1 + -15x) = -2v + -8 Combine like terms: -5 + 1 = -4 -4 + -15x = -2v + -8 Reorder the terms: -4 + -15x = -8 + -2v Solving -4 + -15x = -8 + -2v Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -15x = -8 + 4 + -2v Combine like terms: -4 + 4 = 0 0 + -15x = -8 + 4 + -2v -15x = -8 + 4 + -2v Combine like terms: -8 + 4 = -4 -15x = -4 + -2v Divide each side by '-15'. x = 0.2666666667 + 0.1333333333v Simplifying x = 0.2666666667 + 0.1333333333v
| 5x-2(2x-1)=-12 | | 45x+80=84x+2 | | 12t-9t=15 | | -x+35=-3x+3 | | 14=-(p-11) | | 7(x+6)+7=11x-4(x-6) | | 3(x-)/w=4 | | 11-u=4 | | 14-g=7 | | g(x)=-4x+20 | | Sp=14 | | 23/5n=9 | | -(2x-1)=6x+9 | | 4(k+11)=-12 | | 1/3(2x-1)= | | 200-1.5x=200-2.5x | | 15-4x+3=5x | | t/2+1=16 | | 2/3x3/5 | | 1=q/4-2 | | -6=6z-4 | | -6=6z-4/4 | | 4x^2-4x+39=0 | | 7q-46=180 | | (n-1)p^2-5p-7=0 | | x^2+(2x+8)(2x+8)=(3x-8)(3x-8) | | 6.7z+19.02=-17.6z-18.38+15.8z | | 3v-11-3v=6+5v-9 | | 5(x+7)=7x+8-2x+27 | | 4/3x3.14x27 | | y=-1.2x+22 | | -18.5-17.7j=1.96-15.5j |